Cellular Therapies in Pediatric Liver Diseases - Sunitha Vimalesvaran; Jessica Nulty; Anil Dhawan (Cells, 2022)
Liver transplantation is the gold standard for the treatment of pediatric end-stage liver disease and liver based metabolic disorders. Although liver transplant is successful, its wider application is limited by shortage of donor organs, surgical complications, need for life long immunosuppressive medication and its associated complications. Cellular therapies such as hepatocytes and mesenchymal stromal cells (MSCs) are currently emerging as an attractive alternative to liver transplantation. The aim of this review is to present the existing world experience in hepatocyte and MSC transplantation and the potential for future effective applications of these modalities of treatment.